Protective Role of Saffron (Crocus sativus) against Lead-Induced Toxicity in Poultry and Farm Animals: A Review - Amen, Sameerah H. (American Journal of Botany and Bioengineering, 2025)
Pollution with heavy metals (Pb) is harmful to human and animal health, animal productivity and food safety. Abstract Background Exposure of birds and livestock to environmental lead significantly modifies the anaerobic biochemical pathways, induces oxidative stress and causes organ specific damage, all of which affects growth, reproduction and economic loss. But, the negative effects of these additives made researchers find natural feed additives with potent antioxidant activity as a potential alternative. Background: Saffron (Crocus sativus) is one of the richest sources of bioactive food compound bioactive ingredients (e.g., crocin, crocetin, safranal and picrocrocin) that is effective in lead toxicity. It exerts antioxidant activity through augmenting antioxidant enzyme activity, reducing lipid peroxidation, and maintaining parameters of hematology delivery, immune response and reproductive performance, as indicated by the data from saffron supplementation. Furthermore, its inclusion in animal feeds has the potential to reduce chemical and drugs use and produce sustainable animals’ production of better quality products. In this review, we do not indicate that our hypothesis driven-integrative literature survey is devoid of further focused research on saffron supplementation but depict its nutraceutical prospects based on the putative ameliorative actions (glaring indications of potential if not well-defined actual; dose-dependent, high GrAS dosage toxicity and possible-to-establish concentration gradient toxicokinetics yet to be standardised aided by multinational field trial case studies) against heavy metal toxicity in poultry and farm animals.